2012
DOI: 10.1097/pep.0b013e318267c5cf
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Validity of the Bayley-III and the Peabody Developmental Motor Scale–2

Abstract: The study supports the substitution of the Bayley-III for the PDMS-2 for standard scores or AE scores for children aged 19 to 26 months and for standard scores for children birth to 18 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 7 publications
0
44
0
Order By: Relevance
“…However, there is also evidence to suggest that the Bayley-2 may overestimate impairment, particularly in relation to motor development 22,25,26. A study comparing preterm infant outcome during different eras of Bayley Scales use found Bayley-2 MDI and PDI scores to be lower than when using either previous or later editions 22.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there is also evidence to suggest that the Bayley-2 may overestimate impairment, particularly in relation to motor development 22,25,26. A study comparing preterm infant outcome during different eras of Bayley Scales use found Bayley-2 MDI and PDI scores to be lower than when using either previous or later editions 22.…”
Section: Discussionmentioning
confidence: 99%
“…A study comparing preterm infant outcome during different eras of Bayley Scales use found Bayley-2 MDI and PDI scores to be lower than when using either previous or later editions 22. A lack of concurrent validity has been found between Bayley-2 PDI and the Peabody Developmental Motor Scale II (PDMS-2)25 but a strong correlation was found between Bayley-3 Motor Composite scores and the PDMS-2 26. Moreover, Bayley-2 motor raw scores in preterm infants showed very stable increases from 6 to 24 months,27 but following correction using Bayley-2 norm data, the resulting Bayley-2 PDI scores were unstable over the same time period.…”
Section: Discussionmentioning
confidence: 99%
“…Validity was examined for age differentiation. The correlation coefficients determined for 12-month age intervals ranged from r = .80 to .93, indicating that the subtests were associated with age, consistent with the developmental pattern of motor behaviors (Connolly, McClune, & Gatlin, 2012). At the time of the data collection, no instrument to assess motor development had been translated, adapted or validated for use in Brazil so the English version of PDMS-2 was used.…”
Section: Instrumentsmentioning
confidence: 99%
“…Although the study was designed for a specific country, the methodology used to develop and validate the new tool is applicable in any context, particularly in developing countries. Recently, several validation studies investigated the use of the Bayley scales to evaluate early child development (26)(27)(28)(29); however, many did not cover all Bayley-III domains or only targeted children within specific age ranges. Our study includes all ages that could be assessed with the Bayley-III.…”
Section: Discussionmentioning
confidence: 99%